Incidence and mechanisms of longitudinal stent deformation associated with Biomatrix, Resolute, Element, and Xience stents: Angiographic and case‐by‐case review of 1, 800 PCIs. Issue 6 (24th April 2015) - Arnous, Samer; Shakhshir, Nizar; Wiper, Andrew; Ordoubadi, Farzin‐Farth; Williams, Paul; Clarke, Bernard; Mahadavan, Vaikom; El‐Omar, Magdi; Mamas, Mamas; Fraser, Douglas
Abstract : Background: There is conflicting evidence regarding the incidence of longitudinal stent deformation (LSD) in contemporary practice. Methods and results: To assess the incidence and mechanism of LSD across commonly used DES platforms, we performed a case‐by‐case review of 1, 800 PCI cases involving 450 consecutive procedures using Biomatrix Flex, Resolute Integrity, Promus Element, and Xience V stents, respectively, between January 2009 and December 2011. LSD was detected in a higher proportion with Promus Element [15 (3.1%)] compared with other platforms (Xience V [4 (0.9%)], Biomatrix [3 (0.7%)], Resolute [3 (0.7%)]; P  = 0.002). LSD was characterized as guide catheter/guide extension induced, or as impact from secondary devices such as postdilatation balloons or IVUS catheters. The incidence of guide catheter/guide extension LSD was similar across platforms; (Promus Element [5 (1.1%)], Xience V [4 (0.9%)], Biomatrix [3 (0.7%)], Resolute [3 (0.7%)]; P  = 0.85). Secondary device LSD occurred exclusively with Promus Element (9/450 cases [2%] ( P  < 0.0001). Re‐entering the deformed stent was more difficult in cases of secondary device LSD (6/9 compared with 0/12 treated cases; P  < 0.001). Univariate predictors of LSD were previous CABG, culprit vessel, ostial involvement, and lesion tortuosity. Multivariate predictors of LSD were the Promus Element stent (OR 5.53 CI[1.54–19.85]), Guideliner use (OR 22.09 CI[4.73–103]), postdilation balloons (OR 5.47 CI[1.31–22.81]) and number of stents deployed (OR 2.06 CI[1.45–2.9]. Conclusion: LSD is more common than previously reported. LSD by a guide catheter/guide extension occurred equally with all platforms, however, LSD associated with secondary devices only occurred with the Element stent. These findings have important implications regarding current and future stent designs. © 2015 Wiley Periodicals, Inc.